CORPORATE DEBT RESTRUCTURING IN SCHEDULED COMMERCIAL BANKS IN INDIA: AN ANALYSIS - Agrawal, Gopal Prasad; Kumar Swain, Anil; Kumar Bhuyan, Aswini (International Journal of Research -GRANTHAALAYAH, 2017)
need to see that the level of NPAs is kept down. In spite of many fold developments, adverse development of accumulation of NPAs to place over the period, several tools / methods of managing NPAs were tried such as Lok Adalats, Debt Recovery Tribunals, SARFAESI Act, Corporate Debt Restructuring and many more. Cleaning up of the Bank Balance Sheets is essential and urgent to boost growth in coming years, independent loan review mechanism and sale of unproductive assets are some of the ways to arrest the rising NPAs. Since the quality of advances in India particularly the corporate stressed advances are quite poor and huge in comparison to other Asian Pacific emerging countries, if the NPAs are not managed properly there is every chance that the capital and reserves of Banks shall not to able to meet the losses arising on account of write off of Bad Loans.